2016
DOI: 10.1080/00222895.2016.1241750
|View full text |Cite
|
Sign up to set email alerts
|

Bipedal Hopping Reveals Evidence of Advanced Neuromuscular Aging Among People With Mild Multiple Sclerosis

Abstract: Measures of walking such as the timed 25-ft walk test (T25FWT) may not be able to detect subtle impairment in lower limb function among people with multiple sclerosis (MS). We examined bipedal hopping to determine to what extent people with mild (Expanded Disease Severity Scale ≤ 3.5) MS (n = 13) would differ compared to age-, gender-, and education-matched controls (n = 9) and elderly participants (n = 13; ≥ 70 years old). We estimated lower limb power (e.g., hop length, velocity), consistency (e.g., variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 50 publications
4
15
0
Order By: Relevance
“…Therefore, while the T25FWT was not sensitive enough to detect subtle motor impairment, hopping was able to expose these motor deficits in the same group of individuals. Hopping variables were also predictive of EDSS score (r 2 = 0.38, p = 0.02) (Kirkland et al, 2016). These findings suggest that bipedal hopping may be useful in exposing underlying motor impairment in individuals with low disability scores (Kirkland et al, 2016).…”
Section: Hopping In Msmentioning
confidence: 86%
See 4 more Smart Citations
“…Therefore, while the T25FWT was not sensitive enough to detect subtle motor impairment, hopping was able to expose these motor deficits in the same group of individuals. Hopping variables were also predictive of EDSS score (r 2 = 0.38, p = 0.02) (Kirkland et al, 2016). These findings suggest that bipedal hopping may be useful in exposing underlying motor impairment in individuals with low disability scores (Kirkland et al, 2016).…”
Section: Hopping In Msmentioning
confidence: 86%
“…There has been one study that has measured hopping ability in people with mild MS. This study reported that people with MS display hopping abilities characteristic of an older individual, demonstrating potential early senescence of the neuromuscular system (Kirkland et al, 2016). In this particular study, MS subjects with mild disability as well as age and gender matched controls and elderly subjects performed a two-foot, forward hop at their self-selected pace.…”
Section: Hopping In Msmentioning
confidence: 88%
See 3 more Smart Citations